Text Mining and Visualisation of Post-Covid-19 Metaverse Online News Related to Sports in South Korea - Ju Chan Na; Eun Joung Kim; Jung Yoon Kim, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The concept of the 'Metaverse' gained prominence following the COVID-19 pandemic, which coincided with the resurgence of the virtual world's economic ecosystem and advancements in IT technology. Recent studies have highlighted the significance of examining the establishment of societal perceptions and key social issues surrounding Metaverse in this rapidly advancing era. These studies have analysed popular content, the spread of sports awareness, and successful cases to shed light on this matter. The purpose of this study was to analyse online news data collected from the top three portal sites in South Korea using semantic network text mining technology. The study aimed to emphasise the significance of this data in promoting sports and physical activities. The study's findings indicate the need for collaboration among government ministries, departments, and agencies to facilitate the activation of metaverse-related startups, small and medium-sized enterprises, universities, and research institutes. Additionally, metaverse companies should prioritise the creation of high-quality content and recognise the significance of sports beyond online gaming. This should be accompanied by advancements in 5G-based hardware and software. This study aims to serve as a valuable reference for understanding and preparing for the upcoming metaverse era. It explores strategies for ensuring the sustainable growth of the metaverse across various aspects of life, including sports awareness and prevalence.